Analysis of the Introduction in Clinical Practice of New Oral Anticoagulants in Local Health Agency BT: Translation of the Clinical Trial Data to a Local Health Care Area - Gianluca Grimaldi; Domenica Ancona; Domenico Tricarico; Paolo Stella; Cataldo Procacci; Antonio Germinario; Vito Bavaro; Vito Montanaro; Alessandro Delle Donne (Pharmaceutics, 2021)
The commercial release of the New Oral Anticoagulants (NOACs) has been the most significant change in anticoagulant therapy in recent years. The work aimed to evaluate the economic and health impact for the Local Health Agency Barletta-Andria-Trani (BT). Through the Regional Information System data about naïve patients on NOAC treatment and patients on anti-vitamin-k (VKA), treatments were extrapolated. We assessed therapeutic continuity, pharmaceutical expenditure, hospitalizations, and deaths in 2017 and 2018. Therapeutic continuity was similar in the two groups. The number and the average cost of hospitalizations for a patient treated with VKAs were almost constant, while those of patients treated with NOACs decreased. The treatment of adult-aged naïve patients with NOACs, compared to VKAs therapy, involves an increase in expenditure of about 100€ for a patient, but the reduced hospitalizations could generate, in the long term, saving for the Health System. Clinical data, according to the Real-World Data, confirmed the safety and effectiveness of these drugs. However, attention to the special population is necessary to improve the safety and effectiveness of NOACs. Innovative formulations for pediatric patients are being developed. The challenge for Health Systems is the appropriate use of available resources through health interventions with transversal competences.